1999
DOI: 10.1159/000007642
|View full text |Cite
|
Sign up to set email alerts
|

Embryology of the Pancreatic Duct System

Abstract: Background/Aims: It has been suggested that the distal portion of the dorsal pancreatic duct and the ventral pancreatic duct usually merge into the main pancreatic duct, and the proximal portion of the dorsal pancreatic duct becomes the accessory pancreatic duct. In this study, we investigated the embryology of the accessory pancreatic duct roentgenographically and immunohistochemically. Methods/Results: The accessory pancreatic duct shows two different patterns in pancreatograms: the long and the short type. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 6 publications
1
32
0
1
Order By: Relevance
“…As development progresses embryologically, the duct of the dorsal bud usually undergoes a certain degree of atrophy at its duodenal end and becomes a smaller pancreatic duct [15,16]. Although Santorini’s duct dominance, in which the ventral pancreatic duct is narrower and anastomoses with Santorini’s duct, is observed in about 4% of pancreases [17,18], DPD dominance was detected in 12% of PBM patients.…”
Section: Discussionmentioning
confidence: 99%
“…As development progresses embryologically, the duct of the dorsal bud usually undergoes a certain degree of atrophy at its duodenal end and becomes a smaller pancreatic duct [15,16]. Although Santorini’s duct dominance, in which the ventral pancreatic duct is narrower and anastomoses with Santorini’s duct, is observed in about 4% of pancreases [17,18], DPD dominance was detected in 12% of PBM patients.…”
Section: Discussionmentioning
confidence: 99%
“…They contact each other around day 37 and consequently fuse with each other at the end of week 6 [12]. The junction usually lies within the head of the gland.…”
Section: Discussionmentioning
confidence: 99%
“…The ventral duct communicates with the main duct of the dorsal bud, with the point of union lying between the isthmus and the head of the pancreas. The proximal part of the main dorsal duct partially regresses to form the APD (Santorini’s duct), which opens into the minor duodenal papilla [1,2,3,4,5]. …”
Section: Embryology Of the Pancreatic Duct Systemmentioning
confidence: 99%
“…Fusion of the pancreatic buds is accompanied by anastomosis of the ducts. It has been suggested that the distal portion of the dorsal pancreatic duct and the ventral pancreatic duct usually merge into the main pancreatic duct (MPD), and the proximal portion of the dorsal pancreatic duct becomes the accessory pancreatic duct (APD, Santorini’s duct), which opens into the minor duodenal papilla [1,2,3,4,5]. …”
Section: Introductionmentioning
confidence: 99%